European-wide antimicrobial resistance monitoring in commensal Escherichia coli isolated from healthy food animals between 2004 and 2018. (7th October 2022) - De Jong, Anno; El Garch, Farid; Hocquet, Didier; Prenger-Berninghoff, Ellen; Dewulf, Jeroen; Migura-Garcia, Lourdes; Perrin-Guyomard, Agnès; Veldman, Kees T; Janosi, Szilard; Skarzynska, Magdalena; Simjee, Shabbir; Moyaert, Hilde; et al.
Abstract: Objectives: To describe the susceptibility of Escherichia coli to medically important antibiotics, collected over four periods (2004–2006, 2008–2009, 2013–2014, 2017–2018), from food-producing animals at slaughter. Methods: Intestinal contents from cattle, pigs and broilers were randomly sampled (5–6 countries/host; ≥4 abattoirs/country; one sample/animal/farm) for isolation of Escherichia coli ; antimicrobial susceptibilities were centrally determined by CLSI agar dilution. Clinical breakpoints (CLSI) and epidemiological cut-off values (EUCAST) were applied for data interpretation. Results: In total, 10 613 E. coli strains were recovered. In broilers, resistance percentages were the lowest ( P ≤ 0.01) in the latest time period. A significant decrease in MDR over time was also observed for broilers and a tendency for a decrease for pigs. Resistance to meropenem and tigecycline was absent, and resistance to azithromycin was 0.2%–2.0%. Also, low resistance to third-generation cephalosporins (1.1%–7.4%) was detected in broilers. Resistance to colistin varied between 0.1%–4.8%. E. coli from broilers showed high resistance to ciprofloxacin (7.3%–23.3%), whereas for cattle and pigs this was 0.2%–2.5%. Low/moderate resistance to chloramphenicol (9.3%–21.3%) and gentamicin (0.9%–7.0%) was observed in pigs and broilers. The highest resistance was noted for ampicillin (32.7%–65.3%), tetracycline (41.3%–67.5%), trimethoprim (32.0%–35.7%) and trimethoprim/sulfamethoxazole (27.5%–49.7%) from pigs and broilers, with marked country differences. MDR peaked in pigs and broilers with 24 and 26 phenotypes, with 21.9%–26.2% and 18.7%–34.1% resistance, respectively. Conclusions: In this pan-EU survey antibiotic susceptibility of commensal E. coli varied largely between antibiotics, animal species and countries. Resistance to critically important antibiotics for human medicine was absent or low, except for ciprofloxacin in broilers and ampicillin in pigs and broilers.